2022
DOI: 10.1021/acs.chemmater.2c01444
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Chain Scissionable Resists for Extreme Ultraviolet Lithography: Discovery of the Photoacid Generator Structure and Mechanism

Abstract: Extreme ultraviolet (EUV) lithography currently dominates the frontier of semiconductor fabrication. Photoresists must satisfy increasingly strict pattern fidelity requirements to realize the significant enhancements in resolution offered by EUV technology. Traditional chemically amplified resists (CARs) have hit a barrier in the form of the resolution, line edge roughness, and sensitivity trade-off. This has been compounded by a lack of understanding of the chemical mechanism associated with the EUV process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…This resulted in PPA 3, which possessed two responsive endcaps at the head and tail of the polymer. For comparison, PPA 1 was constructed to bear a phenyl carbonate end-cap known to be inactive 22 under UV radiation. TGA analysis (SI) demonstrated that PPA 2 and 3 still enjoyed good thermal stability, with degradation temperatures of 143 and 147 °C, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in PPA 3, which possessed two responsive endcaps at the head and tail of the polymer. For comparison, PPA 1 was constructed to bear a phenyl carbonate end-cap known to be inactive 22 under UV radiation. TGA analysis (SI) demonstrated that PPA 2 and 3 still enjoyed good thermal stability, with degradation temperatures of 143 and 147 °C, respectively.…”
mentioning
confidence: 99%
“…Despite this undesirable effect, the doseto-clear (DTC) of 90 mJ/cm 2 for PPA 3 far exceeds recent attempts 20 to utilize PPA as a PAG free EUV photoresist where DTC measurements exceeded 10000 mJ/cm 2 . Furthermore, the absence of PAGs in this resist is likely to significantly improve the resolution and line edge roughness beyond the previously developed two component system 22 by eliminating the deleterious effects of acid diffusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported the synthesis of a remarkably stable poly(phthalaldehyde) (PPA) derivative that did not suffer from monomer outgassing associated with the original PPA resist. [21][22][23] This brominated derivative (Br-PPA) was studied with various PAGs to create a resist system that was ultimately limited by acid diffusion and the stochastics of mixing the two components. In this work, we sought to synthesize an improved resist based on Br-PPA that did not require the usage of separate small molecule PAGs to achieve high EUV sensitivity.…”
mentioning
confidence: 99%
“…This resulted in PPA 3, which possessed two responsive end-caps at the head and tail of the polymer. For comparison, PPA 1 was constructed to bear a phenyl carbonate end-cap known to be inactive 22 under UV radiation. TGA analysis (SI) demonstrated that PPA 2 and 3 still enjoyed good thermal stability, with degradation temperatures of 143 ˚C and 147 ˚C, respectively.…”
mentioning
confidence: 99%